2015
DOI: 10.1007/s10021-015-9886-5
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Disturbance Effects of Hailstorm and Fire on Vegetation in a Mediterranean-Type Ecosystem

Abstract: 10Frequency and intensity of disturbance is projected to increase for many ecosystems globally, 11 with uncertain consequences, particularly when disturbances occur in rapid succession. We 12 quantified community response (fifty-two shrub species and the tree Eucalyptus todtiana) to a 13 severe hailstorm followed two months later by prescribed fire for a Mediterranean-type 14 shrubland in southwestern Australia. Partial overlap of hailstorm path and fire perimeter 15 provided a unique opportunity to compare st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 58 publications
(21 reference statements)
0
17
0
Order By: Relevance
“…, Gower et al. ). This could indicate the existence of short‐term synergistic effects of fire and drought if, for instance, forest regeneration is precluded in a drought year right after a large fire (e.g., mortality of recruits; Pratt et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…, Gower et al. ). This could indicate the existence of short‐term synergistic effects of fire and drought if, for instance, forest regeneration is precluded in a drought year right after a large fire (e.g., mortality of recruits; Pratt et al.…”
Section: Discussionmentioning
confidence: 99%
“…The significantly larger effects of consecutive vs. simultaneous events suggest that specific sequences of events may modulate the response of the system (Miao et al 2009, Gower et al 2015. This could indicate the existence of shortterm synergistic effects of fire and drought if, for instance, forest regeneration is precluded in a drought year right after a large fire (e.g., mortality of recruits; Pratt et al 2014) or in a fire year after a drought year (e.g., lack of seed sources; Meng et al 2015).…”
Section: Cumulative Effects Of Fire and Droughtmentioning
confidence: 99%
“…Bigler and Veblen (2011) found that immediately following tree death associated with drought and increased bark beetle activity in northern Colorado, United States, high loads of litter accumulated up to 10 times more for spruce, 5 times for fir and 2 times for pine compared with live trees. Gower et al (2015) reported an increase of nearly 18 tonnes ha -1 under trees and 2 tonnes ha -1 under shrubs following canopy defoliation by an intense hailstorm in Western Australia. The differences in fuel load between our current study and other disturbance investigations are likely to be due to a combination of time since impact, forest types and causal factors.…”
Section: Discussionmentioning
confidence: 99%
“…Linked disturbances, where the likelihood, intensity, or extent of a second disturbance is impacted by the first, are currently receiving a great deal of attention (Buma 2015;Gower et al 2015). For instance, the link between widespread conifer mortality from bark beetles and subsequent fire potential and fire behaviour (Harvey et al2013) continues to be a topic of concern for forest managers and policy-makers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation